IDENTIFICATION OF FISHERMEN'S LIFE ASSET OWNERSHIP IN JANGKA DISTRICT, BIREUEN REGENCY - Suryadi, Suryadi; Adhiana, Adhiana; Riani, Riani; Al Arabi, Rizza (CV. Radja Publika, 2022)
Access to asset ownership is very urgent because it relates to the ease of a person in living his life. The availability of living assets is directly related to the ability of each individual to achieve a more decent life outcome. These living assets are generally categorized into five types, namely human, cultural, financial, social and physical assets. This research was conducted in Jangka District, Bireuen Regency. The number of samples in this study were 100 fishermen. The sampling method used the Accidental Sampling technique, which is the technique of determining the sample by chance. This study uses primary data obtained through a survey using a questionnaire and secondary data. This data was then analyzed qualitatively descriptively. The results of the study found that most of the fishermen were of productive age, had secondary education, quite experienced, used my own financial sources, access to credit was still difficult, had great motivation to improve their standard of living, and the influence of the traditional panglima laot institution was still strong. The main source of capital for the fishermen is borrowing from the owner, cooperatives and only a few have their own capital. But most fishermen have savings, and they save money in the banks, social gatherings, cooperatives and at home, and this is done to save for their lives in the future. Based on physical assets, most fishermen have nets as fishing tools, many use 5-10 GT and 10-20 GT motorboats as fishing boats. Ownership status of fishing boats most fishermen use jointly by riding and renting. From social assets, most fishermen join fishermen's organizations or groups, and a small number of fishermen have positions in the community. The family relationship between them is also close.